2011
DOI: 10.1016/j.bone.2011.03.685
|View full text |Cite
|
Sign up to set email alerts
|

Understanding in vivo response and mechanical property variation in MgO, SrO and SiO2 doped β-TCP

Abstract: The aim of this work is to evaluate the influence of MgO, SrO and SiO2 doping on mechanical and biological properties of β-tricalcium phosphate (β-TCP) to achieve controlled resorption kinetics of β-TCP system for maxillofacial and spinal fusion application. We prepared dense TCP compacts of four different compositions, i) pure β-TCP, ii) β-TCP with 1.0 wt. % MgO + 1.0 wt. % SrO, iii) β-TCP with 1.0 wt. % SrO + 0.5 wt. % SiO2, and iv) β-TCP with 1.0 wt. % MgO + 1.0 wt. % SrO + 0.5 wt. % SiO2, by uniaxial press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 50 publications
3
130
0
2
Order By: Relevance
“…Initiation of osteon formation indicates that osteoid is turning into laminar and osteonic bone. 33,38 Development of osteon formation was observed inside both macro and micro pores as part of the bone modeling and remodeling processes in both pure and dope TCP as shown in Figure 8(a-d). The increased number of osteon and thus haversian canal formation was observed in the newly formed bone in Sr-Mg-doped TCP as compared with pure TCP scaffolds.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Initiation of osteon formation indicates that osteoid is turning into laminar and osteonic bone. 33,38 Development of osteon formation was observed inside both macro and micro pores as part of the bone modeling and remodeling processes in both pure and dope TCP as shown in Figure 8(a-d). The increased number of osteon and thus haversian canal formation was observed in the newly formed bone in Sr-Mg-doped TCP as compared with pure TCP scaffolds.…”
Section: Resultsmentioning
confidence: 91%
“…In our previous study with dense TCP, 33 we have shown that the SrO and MgO co-substitution in b-TCP influences the microstructure, density, mechanical strength, and both in vitro and in vivo bioactivity. This study in line of our recent study in a rat cortical defect model 22 demonstrates the beneficial effects of SrO and MgO doping in 3DP interconnected macro porous TCP scaffolds with multiscale porosity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, β-TCMP was present in glass-ceramics based on 3CaO·P 2 O 5 SiO 2 MgO system via crystallization glass bulk [10]. In recent years, the chemical modification of β-TCP through ionic substitutions has received much attention, considering that major components of biological tissues are composed of a calcium phosphate mineral phase containing a variety of other elements [11]. Mg 2+ is considered the most important ion used in calcium substitution in the crystal structure of β-TCP, leading to a change in the biological and chemical behavior of these materials.…”
Section: Introductionmentioning
confidence: 99%